Comparison of the electro-thermal constraints on SiC MOSFET and Si IGBT power modules in photovoltaic DC/AC inverters. (November 2017) - Dbeiss, Mouhannad; Avenas, Yvan; Zara, Henri
Abstract: This article presents a comparative study between SiC MOSFETs and Si IGBTs regarding changes in their junction temperature in a PV inverter application. The estimation of these variations is made by introducing the current mission profiles extracted from a photovoltaic plant over one year into a calculation tool. The latter is based on a losses model and a thermal model including a coupling between them. The calculation of the losses in SiC MOSFETs in the 3rd quadrant is detailed. The results are the mission profiles of the junction temperature of semiconductors, which allow for determining and comparing the thermal constraints in SiC MOSFET and Si IGBT power modules. Highlights: Si IGBT and SiC MOSFET with same current and voltage ratings are compared. Junction temperatures in a photovoltaic inverter are estimated over one year. Temperature swings and average temperatures are higher in the case of IGBT.